2003
DOI: 10.1016/s0022-0728(03)00354-1
|View full text |Cite
|
Sign up to set email alerts
|

In situ measurement of pH in the interior of conducting polymer microtubules

Abstract: Visible spectral absorption studies of an indicator trapped in the microenvironment of polypyrrole (PPY) and polyaniline (PANI) films were used to investigate the change in pH accompanying changes in oxidation state of the polymer. An indicator, bromophenol blue was incorporated in the conducting polymer film during the electropolymerization process. In situ UV Á/vis spectra of these films were recorded in aqueous solution of KCl. The results obtained show that with increasing potential of the film, the pH of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0
2

Year Published

2007
2007
2015
2015

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 46 publications
0
10
0
2
Order By: Relevance
“…This polymerized form is insoluble, thus resulting in deposition on the working electrode. Prior studies of polymerized BPB describe direct deposition of BPB onto glassy carbon electrodes 24, 25, while deposition on Au electrodes has involved using a supporting polymer matrix such as PPY 21 or PANI 26. However, a high concentration of BPB is desirable to take full advantage of its optical switching properties, making BPB diluted in a supporting polymer matrix less desirable for switching applications.…”
Section: Introductionmentioning
confidence: 99%
“…This polymerized form is insoluble, thus resulting in deposition on the working electrode. Prior studies of polymerized BPB describe direct deposition of BPB onto glassy carbon electrodes 24, 25, while deposition on Au electrodes has involved using a supporting polymer matrix such as PPY 21 or PANI 26. However, a high concentration of BPB is desirable to take full advantage of its optical switching properties, making BPB diluted in a supporting polymer matrix less desirable for switching applications.…”
Section: Introductionmentioning
confidence: 99%
“…For completeness, we begin with a brief summary of the independent parameters generated by softly broken supergravity theories which are needed to test such models at colliders and in dark matter experiments. Comprehensive reviews can be found in [11][12][13]. The conditions under which the soft breaking in the minimal supergravity model are derived are summarized as follows: (i) supersymmetry is broken through a super Higgs effect giving mass to the gravitino through the presence of a hidden sector (singlet); (ii) the hidden and the visible interact only gravitationally; (iii) the Kähler potential is generation independent;…”
Section: Introductionmentioning
confidence: 99%
“…BPB (C 19 H 10 Br 4 S) shows two peaks, one at 436 nm, for the acid form of the indicator and the other at 591 nm, for the basic form. With increase of pH the basic peak at 591 nm increases and the peak at 436 shows a decrease [33]. The indicator was taken in pH 3 phthalate buffer in a quartz cuvette.…”
Section: Uv-vis Studymentioning
confidence: 99%